2005
DOI: 10.1097/01.rct.0000162153.55253.d3
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography Features of Nonspecific Interstitial Pneumonia and Usual Interstitial Pneumonia

Abstract: In contrast to previous reports, NSIP can be separated from UIP in most cases. The presence of honeycombing as a predominant imaging finding is highly specific for UIP and can be used to differentiate it from NSIP, particularly when the distribution is patchy and subpleural predominant. The presence of predominant ground-glass and reticular opacity is highly characteristic of NSIP, but there is a subset of patients with UIP who have this pattern and may require biopsy for differentiation from NSIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 20 publications
4
55
0
2
Order By: Relevance
“…In some previous reports, the most common HRCT finding in NSIP was ground-glass opacity, and consolidation was less common [11,[16][17][18], whereas for Asian patients, NAGAI et al [19] reported that the prevalence of consolidation was 66.7% in fibrotic NSIP. In the present subjects, the prevalence of groundglass opacity and reticulation was almost 100% and consolidation was much less prevalent than ground-glass opacity and reticulation.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous reports, the most common HRCT finding in NSIP was ground-glass opacity, and consolidation was less common [11,[16][17][18], whereas for Asian patients, NAGAI et al [19] reported that the prevalence of consolidation was 66.7% in fibrotic NSIP. In the present subjects, the prevalence of groundglass opacity and reticulation was almost 100% and consolidation was much less prevalent than ground-glass opacity and reticulation.…”
Section: Discussionmentioning
confidence: 99%
“…Since those early clinical studies, the reported occurrence of honeycombing on CT imaging in NSIP has been variable, ranging from 0% to 30% (mean, 20%). (29)(30)(31)(32)(33)(34) In contrast, extensive honeycombing is much more commonly a manifestation of UIP. (35) The findings described above for NSIP are not specific.…”
Section: Pattern 2 Nodulesmentioning
confidence: 99%
“…In large series of pathologically proven UIP [24••, 29], an HRCT pattern of definite UIP was seen in only one third of the cases, whereas more than one third had HRCT appearances suggestive of NSIP. Radiologic diagnosis of NSIP is a challenge, as when experienced radiologists are highly confident that their radiographic diagnosis of NSIP identified underlying histologic NSIP, they are correct 73 % of the time [30]. The absence of honeycombing as the predominating HRCT feature (in the eyes of experienced radiologists) for histologic NSIP has a negative predictive value of 90 % [30].…”
Section: High Resolution Computed Tomographymentioning
confidence: 99%
“…Radiologic diagnosis of NSIP is a challenge, as when experienced radiologists are highly confident that their radiographic diagnosis of NSIP identified underlying histologic NSIP, they are correct 73 % of the time [30]. The absence of honeycombing as the predominating HRCT feature (in the eyes of experienced radiologists) for histologic NSIP has a negative predictive value of 90 % [30]. The presence of concurrent emphysema obscures further the distinction between UIP and NSIP on HRCT [31•].…”
Section: High Resolution Computed Tomographymentioning
confidence: 99%